Analisis Nilai Valuasi Startup Ramerame.co.id Menggunakan Scorecard Method - Dewi, Ayu Sintya (Jurnal Ilmiah Teknologi Informasi Asia, 2024)
Ramerame.co.id is a business collaboration platform that provides opportunities for people to own a business or business with small capital. This research aims to calculate the valuation value of the Ramerame.co.id startup usingScorecard Valuation Method. There are 7 factors assessed, namely: Strength of Entrepreneur and Management Team, Size of Opportunity, Strength of Product and Intellectual Property, Competitive Environment, Marketing/Sales/Partners, Need for additional funding rounds and other Factors Based on the assessment carried out using Based on the assessment carried out using the Scorecard Valuation Method, the valuation value obtained by Ramerame.co.id was IDR 1,881,250,000